Alterations in the expression of IGF‑I isoforms and binding proteins during the wound healing process. (2022) - Garoufalia, Zoe; Papadopetraki, Argyro; Vardakostas, Dimitrios; Karatza, Elli; Philippou, Anastassios; Tsourouflis, Gerasimos; Kouraklis, Gregory; Mantas, Dimitrios
No abstract available